1984
DOI: 10.1002/ijc.2910340205
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer and smoking in males: Types of cigarettes, age at start, effect of stopping and interaction with occupation

Abstract: A case-control study of 512 male cases of bladder cancer and 596 male hospital controls (all living in the province of Turin, Northern Italy) has been analyzed for cigarette smoking. Relative risks (RRs) decreased with years since stopping, whereas they seemed not to change with age starting to smoke. A multiplicative effect of RRs for smoking and high-risk occupations was suggested. Filters exerted a protective effect (RR = 0.3 for smokers of filter-tip cigarettes only vs. smokers of non-filter-tip cigarettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
34
1

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 13 publications
5
34
1
Order By: Relevance
“…High risk of bladder carcinoma appears to be limited largely to cigarette smokers. 3,4,29 The cases in this study also had a high frequency of smoking (83.04% of current smokers). It is suggested that abstinence from smoking to avoid exposure to chemical carcinogens in tobacco is very important for bladder carcinoma prevention and control.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…High risk of bladder carcinoma appears to be limited largely to cigarette smokers. 3,4,29 The cases in this study also had a high frequency of smoking (83.04% of current smokers). It is suggested that abstinence from smoking to avoid exposure to chemical carcinogens in tobacco is very important for bladder carcinoma prevention and control.…”
Section: Discussionmentioning
confidence: 49%
“…Gender was not found to be a risk factor, again in contrast to results from other studies, 26 -28 but men and non-Caucasians have a higher OR. 29 Another risk factor for bladder carcinoma, education, was found to be a risk factor, with less education being a greater risk factor. We observed that both smoking and the duration of smoking increased the risk of bladder carcinoma, consistent with Castelao et al 3 and Vineis et al 29 Many epidemiological studies find that smokers have an overall risk level about 2-4 times that of lifelong nonsmokers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…15 and number of years since cessation, making it difficult to assess the three variables in a case-control design. If the age at start had an effect, we should observe that for a given duration and a given time since quitting the relative risk should differ with age.…”
mentioning
confidence: 99%
“…The relative risk for smoking, however, is the same in the two groups, and it is premature to interpret further these differences. The multiplying effect of occupational exposure and cigarette exposure is also an argument in favor ofthe hypothesis that these exposures affect different stages (15). However, the small number of occupationally exposed individuals would not allow to show small to medium departure from this model.…”
mentioning
confidence: 99%